Hubungan antara Media Pembelajaran Fiqih Menurut Peserta Didik dengan Motivasi Belajarnya di MDA - Fitratul Mutmainnah; Ismaniar Ismaniar (Universitas Negeri Padang, 2018)
The background of this research is the low motivation of learning of students MDA Miftahul Jannah. It is suspected that one of the causes is the use of limited learning media. This research aims to: (1) describes the use of learning medium according to students, (2) describe student’s learning motivation, (3) describe whether there is a relationship between learning medium according to students with learning motivation. The type of this research is quantitative research with a correlational type. The number of population in this study is 70 people. In the sampling technique used stratified random sampling, the sample amounted to 35 people. In collecting data, the techniques used are interviews, and in collecting data used tools such as interview guides. In analyzing the data used the percentage formula and product moment. From the results of the research, it can be seen that in the Miftahul Jannah Jorong Tiakar MDA, Sub-District Guguak District Lima Puluh Kota, (1) the use of instructional media is classified as less and limited, (2) learners' learning motivation is low, (3) between the use of learning media according to students with learning motivation there is a significant relationship.Keywords: Learning Medium, Learning Motivation